Assessing suturing techniques using a virtual reality surgical simulator - Kazemi, Hamed; Rappel, James K.; Poston, Timothy; Hai Lim, Beng; Burdet, Etienne; Leong Teo, Chee (Microsurgery, 2010)
Advantages of virtual‐reality simulators surgical skill assessment and training include more training time, no risk to patient, repeatable difficulty level, reliable feedback, without the resource demands, and ethical issues of animal‐based training. We tested this for a key subtask and showed a strong link between skill in the simulator and in reality. Suturing performance was assessed for four groups of participants, including experienced surgeons and naive subjects, on a custom‐made virtual‐reality simulator. Each subject tried the experiment 30 times using five different types of needles to perform a standardized suture placement task. Traditional metrics of performance as well as new metrics enabled by our system were proposed, and the data indicate difference between trained and untrained performance. In all traditional parameters such as time, number of attempts, and motion quantity, the medical surgeons outperformed the other three groups, though differences were not significant. However, motion smoothness, penetration and exit angles, tear size areas, and orientation change were statistically significant in the trained group when compared with untrained group. This suggests that these parameters can be used in virtual microsurgery training. © 2010 Wiley‐Liss, Inc. Microsurgery 30:479–486, 2010.